Multisided Markets & Platform Dominance - James Alleman; Edmond Baranes; Paul Rappoport (International Telecommunications Society (ITS), 2019)
The internet giants - Facebook, Amazon, Netflix and Google, among others - have transformed society with both positive and negative effects. The negative effects have been stark. There have been huge disruptions caused by e-commerce. More recently, subtler, but even more serious negative effects are only now being recognized: threats to democracy, violations of privacy, and monopolistic behavior. By traditional measures Facebook and Google are highly concentrated. Each has obtained de facto monopolistic or oligopolistic power with little concern on the part of government. Facebook and Google and other internet giants are multisided markets (MSM); their economic rents are "hidden" from the public. On the user-side of the market, prices are zero - "free." On the other side of the market, Facebook's and Google's revenues are derived from advertising which appears when the users click on advertiser's web sites. Facebook and Google can extract exorbitant prices for ads, since they are virtually the only source that can target ads directly to potential customers. This is where the economic rents are not so obvious. This paper addresses the monopolistic/monopsony aspect of the internet giants. In the singlesided market, monopoly pricing is well defined - as well as tests for predatory behavior; not so with multisided markets. Since the definition of markets is central to the legal enforcement of antitrust statutes, the paper examines non-transactional multisided markets for their potential for determining consumers' harm and welfare effects, as well as defining monopoly and predatory pricing in this context. Initial estimates of Google's and Facebook's social cost in terms of consumers' welfare loss are 54 and 33 billion, respectively and increasing cost to consumers at least 87 billion dollars. It demonstrates and quantifies that dominate internet platforms can create three major harms to consumers: - Increasing prices to consumers via added costs to the products being advertised, - Elimination (or non-emergence) of competition in markets to the products being advertised, - Increasing prices to consumers beyond the cost of advertising via the market power of the remaining firms in the market of the products being advertised The paper outlines potential remedies to ameliorate the problems.
Keywords: D42; D43; K21; L12; L13; L22; L51; L96; 330; Advertising; Antitrust; Consumers' Surplus; Internet; Platform Economics; Regulation; Two-Sided/Multisided Markets